Indoor climbing and well-being of young adults: Perspectives among indoor climbers - Elsa C. Osborne; Jeff Rose; Logan Reeves; Kelli Spear; Max E. Coleman; Timothy A. Brusseau Jr; Kathy Franchek-Roa; Akiko Kamimura (PLoS ONE, 2025)
The ongoing mental health crisis among college students raises the necessity of further research on physical, mental, and social well-being; and the role that indoor climbing can play in fostering social connection and improving mental health while also increasing physical fitness. Indoor climbing has many health benefits. Increasing numbers of young adults are involved in indoor climbing; however, research on health and indoor climbing for young adults is lacking. The objective of this qualitative study was to describe indoor climbing and its relationship with the physical, mental, and social well-being of young adults based on perceptions among indoor climbers. Thirty indoor climbers age 18–25 were interviewed from October 2023 to December 2023. The interviews were transcribed and coded using thematic methods. Most participants agreed that indoor climbing positively affected all three areas of their well-being. Themes emerged showing that climbing facilitates a sense of connection, acts as a form of mindfulness, boosts overall mental health, and encourages healthier lifestyles. The results of this study suggest indoor climbing may be effective to promote health among college students and young adults.